Why citizen participation succeeds or fails : a comparative analysis of participatory budgeting - Ryan, Matt (Bristol University Press, 2021)
Matt Ryan draws on ten years of research to deliver this landmark comparative review of participatory budgeting, or collective decisions on spending and taxation around the world. With examples of both positive change and notable failure, the book shows when and why citizens achieve this, and how policy makers can foster democratic engagement.